Akibat Ketidakstabilan Lereng Cekungan Dasar Laut pada Batuan Sedimen Neogen di Desa Kananggar, Kabupaten Sumba Timur, Nusatenggara Timur - Prijantono Astjario (Pusat Survei Geologi, 2006)
Indonesia has thousands of islands in various tectonic settings and, in consequence, it has an immense variety of submarine slopes. Due to the ongoing orogenic processes, Cenozoic basins have emerged, and their evolution can be studied in more detail. Giant slide masses entirely made up of an incoherent association of broken, folded, and crumpled strata occuring along the transect to Kananggar. The best exposed example is located ENE of Kananggar. It follows on top and laterally from a succession of about 100 meter of very thick-bedded, stacked debris, flow-turbidite channels. The slide could be observed 2 in an area of some 10 km . The observed thickness is in order of 120 m and the mass is directly overlain by a normal stratified pelite-turbidite succession.Â Keywords: slope, basin, sea floor, slide, Kananggar